2014
DOI: 10.1007/s10660-014-9159-y
|View full text |Cite
|
Sign up to set email alerts
|

Cross-national heterogeneity in e-retail spending: a longitudinal analysis of economic, technological and political forces

Abstract: Purpose: This paper examines the technological, market, industry and institutional sources associated with the cross-national heterogeneity in e-retail spending.Design/methodology/approach: We used time series cross sectional (TSCS) models linear in parameters for 10 year data from 43 countries to test our hypotheses.Findings: We found that how broadband Internet is accessed, identified as an important determinant of an economy's "e-readiness", explains international heterogeneity in e-retail spending. We also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 62 publications
(68 reference statements)
1
12
0
Order By: Relevance
“…Kshetri et al [26] relied on 10 year panel data from 43 countries and, controlling for GDP per capita, found that consumer propensity to spend on store-based retailing was positive for e-commerce along with broadband. Akhter [27] examined e-commerce expenditure in 43 countries and showed per capita ecommerce expenditure was largely influenced by telecommunications investment and gross national income per capita.…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations
“…Kshetri et al [26] relied on 10 year panel data from 43 countries and, controlling for GDP per capita, found that consumer propensity to spend on store-based retailing was positive for e-commerce along with broadband. Akhter [27] examined e-commerce expenditure in 43 countries and showed per capita ecommerce expenditure was largely influenced by telecommunications investment and gross national income per capita.…”
Section: Related Workmentioning
confidence: 99%
“…[20,23]), others conclude that institutional structures were most relevant (e.g. [24]), while still others point to the salience of socio-economic phenomena [25] and consumer behaviours [26]. In addition, most prior empirical studies considered e-commerce expenditure normalised by GDP, rather than as a proportion of retail.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior researchers have used Euromonitor data in a number of studies (e.g., Blecher, 2010;Coulter et al, 2003;Kshetri et al, 2007;Kopf et al, 2011;Kshetri and Bebenroth, 2012;Kshetri et al, 2014).…”
Section: Data Sourcesmentioning
confidence: 99%